Mortality in a cohort of complex patients with chronic illnesses and multimorbidity: a descriptive longitudinal study. Issue 1 (December 2016) - Martín-Lesende, I.; Recalde, E.; Viviane-Wunderling, P.; Pinar, T.; Borghesi, F.; Aguirre, T.; Recio, M.; Martínez, ME; Asua, J.
Abstract Background Certain advanced chronic conditions (heart failure, chronic lung disease) are associated with high mortality. Nevertheless, most of the time, patients with these conditions are not given the same level of attention or palliative care as those with cancer. The objective of this study was to assess mortality and its association with other variables in a cohort of complex multimorbid patients with heart failure and/or lung disease from two consecutive telemonitoring studies. Methods This multicentre longitudinal study was conducted between 2010 and 2015. We included 83 patients (27 without telemonitoring) with heart failure and/or lung disease with > 1 hospital admission in the previous year and great difficulties leaving home or were housebound. The following variables were indicators of their complex clinical condition: old age (mean: 81 years), comorbidity (Charlson Comorbidity Index score ≥ 2: 86.2 %), both conditions concurrently (54.2 %) and home oxygen therapy (52 %). We assessed mortality (rate, cause and place of death) and its association with: age, sex, telemonitoring, functional status (Barthel score), quality of life (EQ-5D visual analogue scale), number of medications, and all-cause and condition-specific (due to conditions prompting inclusion) admissions during the previous year. Uni- and bivariate analysis and logistic regression were performed, consideringp < 0.05 significant. Results A total of 61 patients died within 5 years, representing 31.2 %/year (95 % CI: 23–40.1 %), considering the overall follow-up (sum of individual follow-up days). Of these, 81 % of deaths (95 % CI: 69.1–89–1 %) were due to the condition prompting inclusion, and 83.3 % (95 % CI: 72–90.7 %) died in hospital (median: 8.5 days). Mortality was lower among those under telemonitoring (p = 0.027), and with fewer condition-specific admissions the previous year (p = 0.006); the latter also showed the strongest association in the multivariate analysis (Exp(B) = 6.115). Conclusions Complex patients with multimorbidity had a high mortality rate, generally dying due to the condition for which they had been included, and in hospital (83.3 %). New approaches for managing such patients should be considered, introducing palliative care as required, and using more comprehensive predictors of mortality (functional status and quality of life), together with those related to the illness itself (previous admissions, progression and symptoms).